Student Absence Following Classical Learning Activities and Roles of Information Services - Adif Jawadi Saputra; Prayitno Prayitno; Yahya Jaya (Global Econedu, 2019)
Many problems the absence of students is one of the things that causes the learning process is not optimal and this becomes an important role of guidance and counseling services through information services. The purpose of this study was to reveal the forms of student absence and the quality of the implementation of information services about absenteeism. This type of research is quantitative descriptive research, the sample used was 123 students using porous sampling technique. Data collected using questionnaire absenteeism and the scale of the implementation of information services about student absence (33 items valid, α = 0.851). Data analysis using percentage analysis and also t-test. The results showed that the most absent form of the students did was not entering school without permission 35 (28.4%) times and the least was days not going to school ie 2 (1.6%) times. The results showed that there was no significant difference in the implementation of information services about student absenteeism both conducted by state high school and private high school teachers with a good category of 71.67%.